The Effect of Covid-19 on the Probability of Default of South African Firms Listed on the Johannesburg Stock Exchange (JSE) - Zille, Nicholas Wolf (Department of Finance and Tax, 2022)
The aim of this study is to quantify and investigate the effect of the Covid-19 pandemic on non-financial South African firms listed on the Johannesburg Stock Exchange. The study implemented the Merton (1974) model on the 59 largest non-financial firms and calculated the probability of default for each firm before the pandemic and during the pandemic as at each firm's financial year-end. The default probabilities are calculated predominantly from the value and volatility of firm equity. The results emphasize that the Covid-19 pandemic, on average, had a dramatic impact on the probability of default of publicly traded South African firms. The observed increase in default probability was found to be statistically significant at the 5% significance level.